Enhanced bending fatigue resistance of a 50CrMnMoVNb spring steel with decarburized layer by surface spinning strengthening. (July 2019) - Ren, C.X.; Wang, D.Q.Q.; Wang, Q.; Guo, Y.S.; Zhang, Z.J.; Shao, C.W.; Yang, H.J.; Zhang, Z.F.
Highlights: Surface decarburized layer of spring steel turns into a strengthened layer after surface spinning strengthening treatment. The bending fatigue life of spring steel with strengthened layer is effectively extended. A fatigue risk model is used to predict the crack initiation site. Surface spinning strengthening treatment decreases the fatigue risk factor in the surface layer. Surface strengthening, controlling inclusion, and homogenizing microstructure can enhance the fatigue resistance of spring steel. Abstract: Surface decarburization directly influences the service performance of spring steel, which is an important scientific issue. The bending fatigue behavior of 50CrMnMoVNb spring steel with surface decarburization as well as treated by surface spinning strengthening (3S) was systematically investigated in this study. The results show that the decarburized layer was significantly modified by turning into a strengthened layer with gradient microstructure after 3S treatment, and the bending fatigue life of spring steel was effectively extended. Furthermore, a fatigue risk model and the Basquin equation were used to predict the crack initiation site and evaluate the fatigue life respectively. Moreover, the 3S treatment can significantly decrease the fatigue risk of the spring steel surface, which makes the fatigue crack initiation site migrate into the subsurface layer and extend the bending fatigue life. Accordingly, some recommended principles were proposed finally to enhance the fatigue resistance of the surface decarburized spring steel, including surface strengthening, removing decarburized layer, decreasing the size and quantity of inclusion, and homogenizing microstructure.